Specific Binding Protein ABCC1 Is Associated With Cry2Ab Toxicity in Helicoverpa armigera - Chen, Lin; Wei, Jizhen; Liu, Chen; Zhang, Wanna; Wang, Bingjie; Niu, LinLin; Liang, Gemei (Frontiers in Physiology, 2018)
A pyramid strategy combining the crystal (Cry) 1A and 2A toxins in Bacillus thuringiensis (Bt) crops are active against many species of insects and nematode larvae. It has been widely used to delay pest adaption to genetically modified plants and broaden the insecticidal spectrum in many countries. Unfortunately, Cry2A can also bind with the specific receptor proteins of Cry1A. ATP-binding cassette (ABC) transporters can interact with Cry1A toxins as receptors in the insect midgut, and ABC transporter mutations result in resistance to Bt proteins. However, there is limited knowledge of the ABC transporters that specifically bind to Cry2Ab. Here, we cloned the ABCC1 gene in Helicoverpa armigera, which expressed at all larval stages and in nine different tissues. Expression levels were particularly high in fifth-instar larvae and Malpighian tubules. The two heterologously expressed HaABCC1 transmembrane domain peptides could specifically bind to Cry2Ab with high affinity levels. Moreover, transfecting HaABCC1 into the Spodoptera frugiperda nine insect cell significantly increased its mortality when exposed to Cry2Ab in vitro, and silencing HaABCC1 in H. armigera by RNA interference significantly reduced the mortality of larvae exposed to Cry2Ab in vivo. Altogether current results suggest that HaABCC1 serves as a functional receptor for Cry2Ab.